2013
DOI: 10.1007/s10803-013-1884-x
|View full text |Cite
|
Sign up to set email alerts
|

Teacher and Child Predictors of Achieving IEP Goals of Children with Autism

Abstract: It is encouraging that children with autism show a strong response to early intervention, yet more research is needed for understanding the variability in responsiveness to specialized programs. Treatment predictor variables from 47 teachers and children who were randomized to receive the COMPASS intervention (Ruble et al. in The collaborative model for promoting competence and success for students with ASD. Springer, New York, 2012a) were analyzed. Predictors evaluated against child IEP goal attainment includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 42 publications
3
74
0
1
Order By: Relevance
“…The principal with low burnout interacted more with staff and teachers, engaged in more personal dialogue, provided more support, and observed others doing their jobs significantly less than the principal at the school with moderate burnout. The importance of administrative support was corroborated by four studies, each of which found relations between principal support and burnout in the expected direction (Embich, 2001;Ruble & McGrew, 2013;Weber & Toffler, 1989;Zabel & Zabel, 2002). The support SETs received from fellow teachers was inversely correlated with burnout (Weber & Toffler, 1989;Zabel & Zabel, 2002).…”
Section: School Level Factors Associated With Burnoutmentioning
confidence: 87%
See 4 more Smart Citations
“…The principal with low burnout interacted more with staff and teachers, engaged in more personal dialogue, provided more support, and observed others doing their jobs significantly less than the principal at the school with moderate burnout. The importance of administrative support was corroborated by four studies, each of which found relations between principal support and burnout in the expected direction (Embich, 2001;Ruble & McGrew, 2013;Weber & Toffler, 1989;Zabel & Zabel, 2002). The support SETs received from fellow teachers was inversely correlated with burnout (Weber & Toffler, 1989;Zabel & Zabel, 2002).…”
Section: School Level Factors Associated With Burnoutmentioning
confidence: 87%
“…Irvin et al (2013) reported SET burnout to be inversely correlated with the number of adult words children with ASD were exposed to in that teacher's classroom setting. Also investigating outcomes for students with ASD, Ruble and McGrew (2013) found inverse correlations between teacher emotional exhaustion and student IEP goal attainment and IEP quality. Further, they found emotional exhaustion accounted for 9.3% of the variance in IEP goal attainment.…”
Section: Burnout and Student Outcomesmentioning
confidence: 99%
See 3 more Smart Citations